The Relationship Between Social Maturity and Sexual Satisfaction, Subjective Well-being, and Controlling Behaviors in Couples: Emphasizing the Mediating Role of Marital Commitment - Hajar Askari Novin; Hamidreza Vatankhah; Javad Khalatbari (Journal of Research & Health, 2022)
Background: Subjective well-being and life satisfaction can help individuals achieve more success in their lives and enjoy better supportive social relationships and higher levels of physical and mental health. The present study aimed to determine the relationship of social maturity with sexual satisfaction, subjective well-being, and controlling behaviors through the mediating role of marital commitment in couples. Methods: The statistical population in this correlational cross-sectional study included all couples in Tehran City, Iran, in 2019, of which 370 people were selected as the sample using a multi-stage cluster sampling method. The research tools included Rao’s social maturity scale (RSMS), the Golombok-Rust inventory of sexual satisfaction (GRISS), the subjective well-being scale (SWS), the controlling behaviors scale (CBS), and the dimensions of commitment inventory (DCI). The obtained data were statistically analyzed by employing structural equation modeling (SEM) in SPSS software, version 23 and LISREL version 8.8. Results: The results showed a positive relationship between sexual satisfaction and social maturity as well as between subjective well-being and social maturity, both mediated by marital commitment (P<0.001). However, a negative relationship was observed between controlling behaviors and social maturity, mediated by marital commitment (P<0.001). Conclusion: Based on the results of the present study, the proposed model had a good fit. Therefore, considering the findings of this study helps researchers and therapists design more appropriate therapies.